High temperature boosts resistant starch content by altering starch structure and lipid content in rice ssIIIa mutants - Zhou, Yufeng; Cheng, Zhenfeng; Jiang, Shuo; Cen, Jinxi; Wu, Dianxing; Shu, Xiaoli (Frontiers in Plant Science, 2022)
High temperature (HT) during grain filling had adverse influences on starch synthesis. In this study, the influences of HT on resistant starch (RS) formation in rice were investigated. Most genes in ssIIIa mutants especially in RS4 were upregulated under NT, whilst downregulated under HT when compared with wild parent R7954. ssIIIa mutants had higher RS content, more lipids accumulation, higher proportion of short chains of DP 9-15 and less long chains of DP37. ssIIIa mutation exacerbated the influences of HT on starch metabolite, caused larger declines in the expression of BEI, BEIIa, BEIIb and SSIVb when exposed to HT. HT reduced the contents of total starch and apparent amylose significantly in wild type but not in mutants. Meantime, lipids were enriched in all varieties but the amounts of starch-lipids complexes and the RS content were only heightened in mutants under HT. HT led to greatest reduces in the amount of DP 9-15 and increases in the proportion of fb3 (DP37), the declines and increases were all larger in mutants, which resulted in varied starch crystallinity. The increased long chains amylopectin and lipids may be the major contributor for the elevated RS content in mutants under HT through forming more starch-lipids complexes (RSV).